Effect of Silica Sand Filter Media Size Variation Towards Turbiding Reduction of Clean Water in PT. XYZ - Fitri, Rahma Izzatul; Hanurawaty, Neneng Yetty; Djuhriah, Naomi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Turbidity is a condition in which the water contains many suspended particles of material that can cause health problems such as itchy skin, red and itchy eyes, and digestive disorders. Based on the initial inspection results, the turbidity value exceeds quality standard Permenkes No. 32/2017, which is 45.2 NTU. The high turbidity value causes the turbid water to need special treatment, one of which is by filtration with silica sand slices as filter media. This study is experimental research using a pre-posttest without a control design. This research aims to determine the effect of turbidity reduction on the variation of silica sand filter media (5–6 mesh), 7–10 mesh, and 11–18 mesh with a height of 60 cm. The population of this research is clean water at PT. XYZ, with as many as 36 samples used in this research. The results of effective and efficient turbidity reduction are on silica sand media measuring 5–6 mesh, with an average percentage of turbidity reduction of 80.49%. The conclusion of this study is the effect of silica sand filter media size variation on turbidity drop of clean water in PT. XYZ. It is recommended for the industry to apply clean water treatment with the filtration method using 5–6 mesh silica sand media, and further researchers are expected to conduct a test regarding the lifetime of the silica sand media that will be used.